2019
DOI: 10.1108/jec-04-2019-0034
|View full text |Cite
|
Sign up to set email alerts
|

Business success factors of Muslim women entrepreneurs in Indonesia

Abstract: Purpose This paper aims to identify important factors affecting the success of Muslim women entrepreneurs (WOE) in the Medan city, North Sumatera province in Indonesia. There are 19 factors that are derived from trait-based, social psychological-based and behavioral-based approaches. Design/methodology/approach A descriptive, exploratory factor and confirmatory factor analyses are used in this study. There are 110 respondents of members of Indonesian Woman Entrepreneur Association and Indonesian Muslim Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 54 publications
2
24
0
6
Order By: Relevance
“…This is the first study to exclusively focus on finding that in the context of a Muslim dominated culture such as Maldives, the causes of success among married and unmarried women managers differ. Rafiki and Nasution (2019) measures the business success factors of Muslim women entrepreneurs in Indonesia and found that more married Muslim women entrepreneurs were going out to work partially due to the burgeoning need for a large work force and also because of economic necessity. Due to labor shortage, more married women have started returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to exclusively focus on finding that in the context of a Muslim dominated culture such as Maldives, the causes of success among married and unmarried women managers differ. Rafiki and Nasution (2019) measures the business success factors of Muslim women entrepreneurs in Indonesia and found that more married Muslim women entrepreneurs were going out to work partially due to the burgeoning need for a large work force and also because of economic necessity. Due to labor shortage, more married women have started returning to work.…”
Section: Discussionmentioning
confidence: 99%
“…• Antecedentes: se refiere a los aspectos que hacen parte de la vida del emprendedor y de su pasado, la experiencia, el círculo social y apoyo familiar entre otros (Nikolić et al, 2019) • Sociodemográficos: son tres factores identificados para este criterio edad, sexo y nivel educativo (Nikolić et al, 2019). • Conducta: CSFF relacionados con las acciones y el comportamiento de un emprendedor a partir de los estímulos que genera el entorno al cual pertenece (Rafiki & Nasution, 2019). • Competencias: son todas las capacidades y habilidades que un tiene un emprendedor, principalmente en cuestiones relacionadas con la creación de empresas (Rafiki & Nasution, 2019).…”
Section: Csff Del Emprendedorunclassified
“…Just as constrained examinations have completed distinguishing the variables which inspire the women to take an interest in the commencement of enterprises gives a superior open door in molding the general public toward gender generalization issues. As per the nation, there is decent variety present in their sociocultural conditions, which prompts the development of social values that may influence pioneering exercises and entrepreneurial behavior of women (Agarwal and Lenka, 2016;Rafiki and Nasution, 2019). The societal values are in charge of the generation of social perception toward women and their endeavor maintainability (Mayasari and Chandra, 2020).…”
Section: Enterprising Community Of Women Entrepreneursmentioning
confidence: 99%